Analisis Qos & Qoe - Fauzan Prasetyo Eka Putra; Mohammad Aziz; Goffal Arifin; Abd Rohman; Abdulloh Rizki; Abd Muiz Syam (Syntax Corporation Indonesia, 2024)
The analysis of quality of service (QoS) and user experience (QoE) has become a major focus in network development. This research adopts a holistic approach to examine the close relationship between QoS and QoE in a rapidly evolving network environment. We review the impact of the interaction between technical aspects (QoS) and user perception (QoE) in the context of multimedia services and high-speed networks. We analyse various QoS evaluation methods as well as factors affecting QoE, considering the dynamics of changes in user preferences. The review covers a wide range of related research conducted by key researchers in this field, including applied models and recent findings related to improving quality of service in modern networks.